The impact of focused attention on bilateral sensory threshold adaptation during unilateral short-term tactile stimulation - Galic, Vladimir; Berić, Aleksandar (Vojnosanitetski pregled, 2025)
Background/Aim. Neuroplasticity of the somatosensory system can be manifested after short-term or long-term peripheral tactile stimulation. Focused attention has been well established as a modulator of neural processing in the visual and auditory systems. However, its role in the primary somatosensory cortex is insufficiently elucidated. The aim of this study was to examine the effect of focused attention on short-term somatosensory neuroplasticity following repeated tactile stimulation of different intensity over identical locations on the hands and shoulders. The aim of the study was also to determine whether repeated tactile stimulation of different intensity in the shoulder area of the non-dominant hand leads to a reduction in the stimulus threshold and to assess whether similar changes occur in the contralateral, unstimulated shoulder somatotopically identical location. Methods. This study included 30 healthy volunteers of both sexes. The contingent negative variation (CNV) wave and the Go/NoGo paradigm for measuring reaction time were used to objectively register the stimulus threshold for light touch, before and after sensory stimulation. The CNV wave was registered within the paradigm with two known stimuli, the first of which was tactile and the second visual in the form of a green or red circle that appeared randomly on the screen. Peripheral sensory stimulation was conducted only over the non-dominant hand and shoulder using multiple series with 12 tactile stimuli of varying intensities. Results. The results showed statistically significant decrease in the stimulus threshold for light touch on both shoulders after tactile stimulation performed only on the non-dominant shoulder. In addition, whenever CNV waves were detected within the Go/NoGo paradigm, reaction times of the subjects were significantly shorter, which served as an objective validation of the initial detection of tactile thresholds before and after peripheral sensory stimulation. Conclusion. Short-term, unilateral tactile stimulation leads to bilateral, functional adaptation of the proximal regions of the upper extremities, which suggests interhemispheric homologous transfer within the somatosensory system, supporting the principle of somatotopic organization in somatosensory neuroplasticity.
Keywords: cerebral cortex; electroencephalography; neuronal plasticity; sensory thresholds